Updating tk−1 is significant to Caputo fractional order switching systems: A reply to Hu's comments. (May 2022) - Wu, Cong; Liu, Xinzhi
Abstract: This is to reply the concerns about our NAHS paper "Lyapunov and external stability of Caputo fractional order switching systems" pointed out by Hu in "Comments on 'Lyapunov and external stability of Caputo fractional order switching systems"' recently.